WOMEN AND CORPORATE TRANSPARENCY: CHALLENGES IN ANTI-BRIBERY AND CORRUPTION POLICIES - Siska; Susanti, Efi; Yesitasari; Putri Juleta, Tiara Amanda (Faculty of Economics and Business University of Mataram, 2025)
This research aims to evaluate the effect of an independent board of commissioners on the disclosure of bribery and corruption policies and to test whether gender diversity moderates these relationships in the short and long term. This research addresses the empirical gap in Indonesia concerning the role of gender diversity in increasing transparency. The method used is the Panel Vector Error Correction Model (PVECM) on 42 public companies in Indonesia during the 2021–2023 period, with data obtained from Refinitiv Eikon DataStream. The findings indicate that the presence of an independent board of commissioners is significant in the long-term disclosure of bribery and corruption policies, but gender diversity cannot moderate these relationships. Research highlights the importance of empowering women on boards to meaningfully improve supervisory functions.